Comparison of clinical efficacy of intrathecal ropivacaine versus ropivacaine with dexmedetomidine in patient posted for infraumbilical surgeries under spinal anesthesia - Yadav, Isha; Aggarwal, Ankita; lakhanpal, Mahima; Nirvan, Himanshu (Asian Journal of Medical Sciences, 2022)
Background: Data related to clinical efficacy of intrathecal dexmedetomidine as an adjuvant to isobaric ropivacaine in spinal anesthesia were found to be inadequate, but the efficacy of newer molecules as an adjuvant is investigated constantly. Considering the favorable profile of dexmedetomidine, it could have a potential role as an adjuvant to ropivacaine. Aims and Objectives: The aim of the study was to evaluate the benefits of adding intrathecal dexmedetomidine as an adjunctive along with ropivacaine. The aim of the study was to assess and compare the safety and efficacy, post-operative analgesia, complications, duration of analgesia, and time of rescue analgesia for intrathecal ropivacaine versus a combination of intrathecal ropivacaine with dexmedetomidine. Materials and Methods: An observational study was carried out in 80 patients of either sex between 25 and 60 years of age, ASA Grade 1 and 2, undergoing elective abdominal, and lower limb surgeries. Subjects selected as per set inclusion/exclusion criteria and divided into two groups for spinal anesthesia. Group A: 3 ml of intrathecal 0.75% isobaric ropivacaine with 0.5 ml of normal saline. Group B: 3 ml of intrathecal 0.75% isobaric ropivacaine with 5 mcg preservative free dexmedetomidine in 0.5 ml of normal saline. Vital parameters were noted at 0 min, 1 min, 2 min, 5 min, 10 min, and thereafter every 15 min, till the surgery continued. Onset and the time for maximum sensory blockade were assessed and VAS scoring was done every 10 min till 30 min and thereafter every 15 min. The duration of effective analgesia was recorded along with the duration of sensory regression to S1, and time for administration of rescue analgesia was noted. Results: The combination of ropivacaine with dexmedetomidine was statistically found to be efficacious when compared to ropivacaine alone, as evidenced by statistically significant differences (P<0.05) in VAS scores at 80, 180, and 360 min and duration of regression to S1 level. The differences in time for rescue analgesia were also statistically significant (P<0.05), further proving the advantage for longer lasting analgesia without any additional adverse effects. Conclusion: 5 mcg dexmedetomidine is an attractive alternative as an adjuvant to spinal ropivacaine in surgical procedures, as opposed to ropivacaine alone, without any additional adverse effects.